Pengaruh Budaya dan Kepercayaan Merek Terhadap Pengambilan Keputusan Mahasiswa Memilih Kuliah di Institut Manajemen Wiyata Indonesia - Mariati Tirta Wiyata; Nova Nuraini Awaliah (Institut Manajemen Wiyata Indonesia, 2019)
This study aims to determine: (1) the influence of culture on student decision making, (2) the influence of brand trust on student decision making, and (3) the influence of culture and brand trust on student decision-making. The subjects of this study were all students of the Institut Manajemen Wiyata Indonesia. The number of respondents in this study were 174 people. Methods of data collection through surveys using questionnaires. The data analysis technique used in this study is Multiple Linear Regression Analysis. The results of the study show that (1) culture influences positively and significantly on student decision-making with a value of 5.430> 1.974 and a significance value of 0.000 <0.05; (2) brand trust has a positive and significant influence on student decision-making with a value of 3.887> 1.974 and a significance value of 0.000 <0.05; (3) simultaneous culture and brand trust have a significant effect on decision making students with a value of 43.97> 0.10 and a significance value of 0.000 <0.05.